Evidence map of ductal carcinoma in situ management options. Issue 11 (November 2019) - Bouskill, Kathryn; Hempel, Susanne; Richardson, Andrea; Ganz, Patricia A.; Baxi, Sangita; Zutshi, Rushil; Larkin, Jody; Motala, Aneesa; Miles, Jeremy N. V.; Crandall, Carolyn J.
Abstract: Objective: Ductal carcinoma in situ (DCIS) has the potential to progress to invasive carcinoma. The optimal management of DCIS and methods for individualizing treatment of DCIS are still being determined. This evidence map depicts the robustness and topical span of research on DCIS management choice on patient-centered and clinical outcomes. Methods: We searched PubMed, EMBASE, PsycINFO, PubMed Health, PROSPERO, and clinical practice guideline sites to identify systematic reviews of DCIS management options and consulted with topic experts. A bubble plot visualizes the literature volume and research content for patient-centered outcomes. An online decision tree facilitates discussions with patients and guides through the available evidence. Results: In total, 40 systematic reviews met inclusion criteria. The research syntheses addressed DCIS management options, including the role of magnetic resonance imaging, axillary surgery/sentinel lymph node biopsy, and excisional biopsy. The map shows existing evidence for mutually exclusive treatment options including active surveillance, breast-conserving surgery, nipple sparing mastectomy, and simple mastectomy. Research findings for intraoperative radiation, adjuvant radiation therapy, adjuvant hormone therapy, hypofractionation radiotherapy, accelerated partial breast irradiation, radiation therapy plus boost, and combined radiation and hormone therapy, as well as for breast reconstruction after mastectomy and surveillance mammography postsurgery are also displayed. The evidence map highlights a scarcity of robust evidence on patient-centered outcomes. Conclusions: The evidence map provides an overview of DCIS research showing the range of management options and remaining decisional dilemmas that follow a diagnosis of DCIS. It maps the evidence in accessible tools to guide practice and future research. N/A: Video Summary: http://links.lww.com/MENO/A448 . Abstract : Supplemental Digital Content is available in the text